2017
DOI: 10.1071/an15215
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance and herd growth potentials of cattle in the Borana pastoral system, southern Ethiopia

Abstract: The pastoral communities in the Borana rangelands of southern Ethiopia mainly rely on cattle (Bos indicus) for their livelihoods. The reproductive performance of cattle is affected by environmental variability and mobility practices that affect fodder availability. This study was conducted to investigate the reproductive performances and herd growth potentials of cattle reared in three ecologically varied zones of Golbo, Malbe and Dirre in the Borana rangelands with different levels of mobility constraints. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Currently three aspects in the Borana pastoral production context e settlement density, concentration of livestock around settlements and increased year round use areas e are likely to contribute to reduced feed availability and resource degradation. It has been shown that the cattle reared in the Dirre zone of the Borana rangelands with lowest mobility have significantly lower reproductive performances and reduced lifetime performance (Wario et al 2015b).…”
Section: Adapting Mobility Patterns To Reduced Grazing Spacesmentioning
confidence: 99%
“…Currently three aspects in the Borana pastoral production context e settlement density, concentration of livestock around settlements and increased year round use areas e are likely to contribute to reduced feed availability and resource degradation. It has been shown that the cattle reared in the Dirre zone of the Borana rangelands with lowest mobility have significantly lower reproductive performances and reduced lifetime performance (Wario et al 2015b).…”
Section: Adapting Mobility Patterns To Reduced Grazing Spacesmentioning
confidence: 99%
“…Several studies have reported that the parameters of the S/C at the smallholder in Indonesia more than 12 months (Agus and Widi, 2018;Priyanti et al, 2015;Rohyan et al, 2016). Some factors that can cause the length of CI include; production system (Gebrekidan et al, 2016), lack of feed availability in the dry period phase (Wario et al, 2017), the length of postpartum estrus (Manzi et al, 2018), number of services per conception (Vinothraj et al, 2016).…”
Section: Reproductive Performance Of Beef Cattle In Different Productmentioning
confidence: 99%